(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the cognitive issue of shaping a person’s artistic creativity. It highlights and analyzes the cognitive significance of artistic creation as an important aspect of a person’s spiritual and practical activity. It has been argued that artistic activity is one of the most unexplored problems in terms of cognition, and that the scientific study of this topical issue is of great importance in the field of education today.